Strategi Sistem Informasi Telkom Akses dengan Analisis Porter’s Five Forces dan Value Chain untuk Keunggulan Kompetitif - Anugra Perdana; Eka Putri Nur Kumal; Nazua Alkhaf; Sugeng Sugeng; Nining Ariati (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Telkom Akses is a company that plays a role in providing fiber optic-based telecommunications infrastructure in Indonesia. With increasing competition in the telecommunications industry, information system-based strategies are the key to creating competitive advantage (Damayanti et al., 2020). This study uses the Porter's Five Forces and Value Chain approaches to analyze Telkom Akses's competitive position (Mardiana, 2023) and identify the application of information systems in each of its business activities. The results of the study show that the use of technologies such as Big Data, AI, IoT, Blockchain, and SDN (Software-Defined Networking) can improve operational efficiency, strengthen customer service, and support service innovation (Aminah, 2022).